MENYIAPKAN RUANGAN DIKLAT SEBAGAI SUMBER BELAJAR YANG KONDUSIF - Miyarso, Estu (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Place or training room have some functions among others as facilities and basic facilities or facility, source of learning, centre of activities, and barometer assess presstige organizer of training. Management of training place cover planning activity, organizational, execution, and monitoring. Some training room criteria which must be paid attention for example; Accesible Comfortable, Quite, private, free and, Space in Around easily move to trainees for Sufficient also have some nature of becoming conditions that is; flexible, isolasif or free from various trouble, settlement of enough light, and existence of adequate ventilation. Arrangement of class room and seating room influence the way discussion, and in turn influence also leadership pattern appearance in group able to streamline result of from target learn or target of training broaderly.